Esophageal Stent in Sleeve Gastrectomy Leak Treatment: Observations Based on a Challenging Surgical Case and Literature - Frattini, Francesco; Rizzi, Andrea; Segato, Sergio; Cortellezzi, Claudio Camillo; Rota Bacchetta, Gian Luca; Cassinotti, Andrea; Gianazza, Simone; Conti, Lorenzo; Carrano, Francesco Maria; Rausei, Stefano (Surgeries, 2021)
Gastric leak is a serious complication of sleeve gastrectomy with a well-documented morbidity and mortality. Depending on the series the leak rate ranges between 1 and 5%. The treatment of sleeve gastrectomy leak is still challenging. Different procedures have been described in management of gastric leak, both surgical and endoscopic. The treatment of gastric leaks depends on the extent of the staple-line leak, the site of the leak and its association with stenosis. As published data are limited, there are no still standardized guidelines on best treatment. One of the most commonly used option in the treatment of gastric leak is esophageal stent. Its success rate reaches 70–80% but it is burdened by some complications. Stent migration is the most common complication in the placement of esophageal stent.We present a challenging surgical in which case the use of an esophageal stent for the treatment of a sleeve gastrectomy leak gained the resolution of the leak but was complicated by bowel obstruction due to migration of the stent.